In Vivo Analysis of Tissue S-Nitrosothiols in Pediatric Sepsis - Daniel T. Cater; Charles Clem; Nadzeya Marozkina; Benjamin Gaston (MDPI AG, 2024)
S-nitrosothiols are endogenous, bioactive molecules. S-nitrosothiols are implicated in many diseases, including sepsis. It is currently cumbersome to measure S-nitrosothiols clinically. We have previously developed an instrument to measure tissue S-nitrosothiols non-invasively using ultraviolet light. We have performed a prospective case control study of controls and children with sepsis admitted to the PICU. We hypothesized that tissue S-nitrosothiols would be higher in septic patients than controls. Controls were patients with no cardiopulmonary instability. Cases were patients with septic shock. We measured S-nitrosothiols, both at diagnosis and after resolution of shock. A total of 44 patients were enrolled: 21 controls and 23 with sepsis. At baseline, the controls were younger [median age 5 years (IQR 0, 9) versus 11 years (IQR: 6, 16), p-value = 0.012], had fewer comorbidities [7 (33.3%) vs. 20 (87.0%), p-value < 0.001], and had lower PELOD scores [0 (IQR: 0, 0) vs. 12 (IQR: 11, 21), p-value < 0.001]. S-nitrosothiol levels were higher in sepsis cohort (1.1 ppb vs. 0.8 ppb, p = 0.004). Five patients with sepsis had longitudinal measures and had a downtrend after resolution of shock (1.3 ppb vs. 0.9 ppb, p = 0.04). We dichotomized patients based on S-nitrosothiol levels and found an association with worse clinical outcomes, but further work will be needed to validate these findings.